How Integrated is Integrated Reporting? From a Malaysian Perspective - Benedict Valentine Arulanandam; Yan Ran Lee (SRIWIJAYA INTERNATIONAL JOURNAL OF DYNAMIC ECONOMICS AND BUSINESS, 2021)
The lack of coherence, transparency and accountability in traditional financial reporting, led the International Integrated Reporting Council (IIRC) to developed Integrated Reporting (IR) in 2010. This study draws the attention towards the top 50 public listed companies listed in Malaysian Stock Exchange as per asset size, and their fulfilment towards voluntary IR disclosures. This study was also conducted to examine the organisational characteristics that foster the IR initiative. A comparison was made with ISO 26000, GRI G4 and IR framework against the annual reports. This study was qualitative and descriptive in nature. The findings revealed that although there were traces of the fulfilment of all requirements with regard to ISO 26000, GRI and IR respectively, there were much to be done to encourage PLCs to incorporate such reporting guidelines. It was also found that, government-linked companies have greater fulfilment of these requirements.